Does the past dictate the future? Exploring the impact of employability programmes on adults experiencing multiple disadvantage. Issue 5 (4th July 2022) - Paterson-Young, Claire; Hazenberg, Richard
ABSTRACT: The research explored the impact of an employability programme, delivered by a Community Interest Company and other third sector partners in England. The programme was designed to increase the employability of people aged between 16–72 years-old who were unemployed or economically inactive. To measure the impact of the programme on participants, 1, 098 people engaging in the project completed questionnaires designed to capture demographic data and measure general self-efficacy (GSE) upon joining the programme (Time 1); whilst 163 of the same participants completed the questionnaire upon completing the programme (Time 2). Interviews were conducted with 26 participants engaged with the programme. Results of the questionnaire data analysis revealed a statistically significant relationship between levels of disadvantage experienced by the participants and GSE at Time 1; statistically significant increases in GSE levels between Time 1 and Time 2 for participants who completed the programme; and a statistically significant relationship between GSE at Time 2 and employment/training outcomes. Triangulation of the quantitative and qualitative results revealed the positive impact of the programme on participant's self-efficacy and employability. This paper is the first of its kind in the UK to explore the impact of employability programmes on adults experiencing multiple disadvantage.